(untitled) (Revista da Faculdade de Odontologia - UPF, 2014)
Objective: This study aimed to analyze the influence of the instrumentation technique (hand or rotary), and apical enlargement on calcium hydroxide (CH) fillings in curved canals. Materials and method: One hundred and ten simulated root canals were divided into eleven experimental groups (G). Canals were prepared with K-Flexofile hand instruments, using either crown-down (GCD 25, GCD 30 and GCD 35) or step-back (GSB 25, GSB 30 and GSB 35) techniques; and with rotary instruments, using either ProTaper (GPT F1 and GPT F2) or K3 (GK3 25, GK3 30 and GK3 35) systems. The apical diameter correspon- ded to 0.20 mm (GPT F1), 0.25 mm (GCD 25, GSB 25, GPT F2 and GK3 25), 0.30 mm (GCD 30, GSB 30, GK3 30), and 0.35 mm (GCD 35, GSB 35, GK3 35). A CH paste, previously colored with blue Indian ink, was injected into the canals using a special syringe. The four sides of the blocks with simulated canals were scanned and the images were transferred to the AutoCAD-2008 software, for assessing the amount (%) of filling in the apical 5 mm (ANOVA; Tukey’s Test; Î±=0.05). Qualitative analysis was also performed regarding the presence or absence of voids (Chisquare Test; Î±=0.05). Results: In GSB, there was significant difference between diameters 25 and 30. GSB showed lower amount of filling (P